1994
DOI: 10.1084/jem.179.1.347
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-mediated regulation of chronic intestinal helminth infection.

Abstract: Most inbred strains of mouse infected with the intestinal nematode Trichuris muris are resistant to infection expelling the parasite before adult worms establish. However, a few susceptible strains exist that are incapable of worm expulsion and harbor chronic infections of mature adult worms. Analyses of in vitro cytokine production by cells from the draining lymph node (mesenteric lymph node) have indicated that expulsion phenotype is tightly correlated with the selective expansion of helper T cells (Th) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
336
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(362 citation statements)
references
References 33 publications
(24 reference statements)
24
336
0
2
Order By: Relevance
“…The naturally occurring mouse counterpart Trichuris muris has provided much information on the immunoregulatory mechanisms underlying resistance and susceptibility to this parasite. A number of studies have shown that the ability to develop resistance or chronicity is dependent on Th2 and Th1 cells, respectively [1,2,4,25]. Our data now demonstrate that IL-1 is a crucial component in the Th2 cytokine cascade that leads to protective immunity and resistance.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The naturally occurring mouse counterpart Trichuris muris has provided much information on the immunoregulatory mechanisms underlying resistance and susceptibility to this parasite. A number of studies have shown that the ability to develop resistance or chronicity is dependent on Th2 and Th1 cells, respectively [1,2,4,25]. Our data now demonstrate that IL-1 is a crucial component in the Th2 cytokine cascade that leads to protective immunity and resistance.…”
Section: Discussionsupporting
confidence: 63%
“…Resistance to T. muris, as measured by worm expulsion, is known to be Th2 dependent [1][2][3][4][5][6]. As expected, the WT mice developed resistance to T. muris infection and expelled the majority of worms before day 18 p.i.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…These changes in the environment of the large intestine are driven by the Th2 cytokine IL-13 and to a lesser extent 24]. In contrast, mice that develop a Th1 response remain susceptible and infection proceeds to chronicity [25]. In this context, IL-10-deficient mice infected with T. muris mount a Th1 immune response and develop a severe inflammation of the large intestine, resulting in the death of the mice [26].…”
mentioning
confidence: 99%